The History Of The Officer’s Position And Its Role In The Formation Of Military Servants - Ruzmet Muratovich Makhmudov; Laziz Izzatillaevich Akbarov (The American Journal of Social Science and Education Innovations, 2021)
The article provides a detailed analysis of the history of the officer’s position, issues of training professional officers, their role in the formation of military personnel with the help of data from the scientific literature.